2011
DOI: 10.1177/147323001103900426
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin Levels are Elevated in Patients with Asthma

Abstract: Osteopontin (OPN) plays a role in T cellmediated immunity, but its involvement in Th2-associated allergic responses, especially asthma, has not been investigated. This cross-sectional casecontrol study was designed to determine whether serum OPN levels are elevated in asthma patients and whether these correlated with disease severity. Serum samples were obtained from patients with mild (n = 42), moderate (n = 48) and severe (n = 39) asthma, and 41 healthy control subjects. OPN protein concentrations were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
(27 reference statements)
0
9
1
Order By: Relevance
“…In the previous study (12), the mean serum OPN levels (15.4 ± 6.2 ng/mL) were relatively low compared to our data and other previous data (14). Commercial ELISA kits are available to determine plasma or serum OPN levels.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…In the previous study (12), the mean serum OPN levels (15.4 ± 6.2 ng/mL) were relatively low compared to our data and other previous data (14). Commercial ELISA kits are available to determine plasma or serum OPN levels.…”
Section: Discussioncontrasting
confidence: 86%
“…The baseline rise in circulating OPN levels was associated with coronary artery disease with rapid plaque progression (16), asthma (14, 17), and cancer aggressiveness and poor survival (2) in humans. Our data demonstrate that high serum OPN levels were associated with osteoporosis, especially in postmenopausal women, suggesting the role of OPN in bone remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…In several other studies conducted in adult patients with asthma, OPN levels were found to be increased in serum, saliva and BALF. 22,23 Regarding IL-17, our results revealed that the IL-17 levels in asthmatic children were higher than those of the control group. IL-17 expression has been shown to increase in sputum, lung, BALFs, and peripheral blood of asthmatic patients.…”
Section: Discussionmentioning
confidence: 61%
“…Osteopontin (OPN) is a multifunctional cytokine that can be expressed by eosinophils and implicated in allergic airway responses. The levels of OPN were elevated in serum of asthmatic patients, but its concentration did not correlated with disease severity . The chemokine RANTES, a key chemotaxis element in allergic airway inflammation, was significantly increased in patients with severe asthma.…”
Section: Biomarkers In Asthmamentioning
confidence: 90%
“…The levels of OPN were elevated in serum of asthmatic patients, but its concentration did not correlated with disease severity. 60 The chemokine RANTES, a key chemotaxis element in allergic airway inflammation, was significantly increased in patients with severe asthma. The serum level of RANTES was associated with eosinophil count and total serum IgE level and displayed inverse relationships with FEV1.…”
Section: Biomarkers In Bloodmentioning
confidence: 99%